MULTIPATH MITIGATION TECHNIQUES IN SATELLITE NAVIGATION FOR PRECISE LANDING - G. V. Krinitsky; M. D. Leonova; E. N. Yurasova (Научный вестник МГТУ ГА)
There are a lot of methods of multipath mitigation, however none of them guarantee its full elimination. The complex method of multipath mitigation in the context of precise aircraft landing is presented in this article.